Transport planning and traffic engineering - O'Flaherty, C. A. (CRC Press, 2018)
Transport Planning and Traffic Engineering' is a comprehensive textbook on the relevant principles and practice. It includes sections on transport policy and planning, traffic surveys and accident investigation, road design for capacity and safety, and traffic management. Clearly written and illustrated, the book is ideal reading for students of transport, transport planning, traffic engineering and road design. This new book, written by senior academics in the field of transport, is a worthy successor to the widely acclaimed first volume of O'Flaherty's Highways. The content has been expanded and thoroughly updated to reflect the many changes that have taken place in this topical area.